APPLICATION OF ANGKOLA BATAK CUSTOMARY CRIMINAL LAW TOWARDS THE CRIMINAL ACT OF MILD THEFT FROM THE PERSPECTIVE OF THE NATIONAL CRIMINAL CODE - Rahmat Akbar Hamonangan Nasution; Mhd Teguh Syuhada Lubis (Inspiring Law Journal, 2026)
Customary criminal law is a law that lives and develops in society, including in the Batak Angkola indigenous community. The application of Batak Angkola customary criminal law to the crime of petty theft has little difference from the application of conventional criminal law, especially after the issuance of the National Criminal Code which prioritizes sanctions in contrast to customary criminal law which prioritizes mediation and discussion between the two parties, in the latest national criminal code, customary law is set aside in its criminal structure, where conventional criminal law is the main point in the basis for the implementation of criminal law in Indonesia.Based on the research results, this study discusses the position of Batak Angkola customary criminal law in the Indonesian criminal law system, its application to petty theft crimes, and its existence from the perspective of the National Criminal Code. Batak Angkola customary criminal law is recognized as a living law in society and has a complementary position in the national legal system. In practice, the resolution of petty theft crimes is carried out through customary deliberations involving traditional leaders, perpetrators, victims, and families based on the values of Dalihan Na Tolu, and provides sanctions in the form of compensation, customary fines, or social sanctions aimed at restoring social harmony. However, the implementation of customary criminal law still faces obstacles such as the influence of modernization, reduced understanding of customary values, and the dominance of national criminal law. Therefore, synergy is needed between customary law and national law so that customary law continues to exist and is effective in resolving conflicts in society.